2021
DOI: 10.1111/1742-6723.13814
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients presenting with low back pain to a private hospital emergency department in Melbourne, Australia

Abstract: Objective: Recent studies suggest many patients with non-specific low back pain presenting to public hospital EDs receive low-value care. The primary aim was to describe management of patients presenting with low back pain to the ED of a private hospital in Melbourne, Australia, and received a final ED diagnosis of non-specific low back pain. We also determined predictors of hospital admission. Methods: Retrospective review of patients who presented with low back pain and received a final ED diagnosis of non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
(34 reference statements)
1
21
0
Order By: Relevance
“…These back pain presentations via ambulance are an average of AUD$449 more costly to the hospital system when a patient is discharged, and an average of AUD$1,812 more costly when a patient is admitted to hospital, compared to non-ambulance presentations [6]. Interestingly, these presentations are less likely to be triaged as 'emergency' or 'urgent' patients compared to those who arrived using other modes [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These back pain presentations via ambulance are an average of AUD$449 more costly to the hospital system when a patient is discharged, and an average of AUD$1,812 more costly when a patient is admitted to hospital, compared to non-ambulance presentations [6]. Interestingly, these presentations are less likely to be triaged as 'emergency' or 'urgent' patients compared to those who arrived using other modes [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, back pain presentations that arrive by ambulance are more likely to receive lumbar imaging, opioid medications and hospital admission regardless of hospital setting (e.g. public or private hospital) [3,5]. These back pain presentations via ambulance are an average of AUD$449 more costly to the hospital system when a patient is discharged, and an average of AUD$1,812 more costly when a patient is admitted to hospital, compared to non-ambulance presentations [6].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite the recommendation from clinical guidelines, recent studies in Australian EDs found that opioids were administered to 55% of patients with non-traumatic musculoskeletal pain and nearly 70% of patients with low back pain. [6][7][8] Oxycodone alone was provided to 57% of patients presenting to Australian EDs with low back pain. 7…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite the recommendation from clinical guidelines, recent studies in Australian EDs found that opioids were administered to 55% of patients with non-traumatic musculoskeletal pain and nearly 70% of patients with low back pain. [6][7][8] Oxycodone alone was provided to 57% of patients presenting to Australian EDs with low back pain. 7Adverse outcomes related to opioid therapy for pain management have been reported in the literature.Recent studies showed that opioid-naïve patients with low back pain who were administered or prescribed opioid in the ED were more likely to have continued opioid use at six-months after the index ED visit.…”
mentioning
confidence: 99%
“…2 Low back pain was the sixth most prevalent primary diagnosis for visiting a public hospital in Australia in 2017-2018. 3 Physical, occupational, and psychosocial all have a role in LBP risk factors. People with physically demanding employment, physical and mental illnesses, smokers, and obese people are more likely to experience low back discomfort.…”
Section: Introductionmentioning
confidence: 99%